MODERN METHODOLOGICAL FOUNDATIONS FOR TEACHING INFECTIOUS AGENTS CAUSING PURULENT INFLAMMATION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This scientific article examines the etiology, pathogenesis, and clinical significance of infectious agents responsible for purulent inflammatory processes. In addition, modern methodological approaches to teaching this topic in higher medical education institutions are analyzed. Particular attention is given to pedagogical technologies based on problem-based learning, competency-oriented education, and the development of clinical reasoning skills from the perspective of an infectious disease specialist.